2017
DOI: 10.1371/journal.pone.0183682
|View full text |Cite
|
Sign up to set email alerts
|

Rooibos (Aspalathus linearis) extract enhances boar sperm velocity up to 96 hours of semen storage

Abstract: Rooibos (Aspalathus linearis) is a native shrub from South African fynbos and has become very popular in the last decades for its antioxidant and medicinal attributes. Several studies have shown its beneficial properties in numerous cell lines, but to date, the in vitro effects of rooibos extract on sperm cells are still unknown. In this study, boar semen was supplemented with four concentrations both of fermented and unfermented rooibos extracts during 96 h of liquid storage at 17°C. The effects of rooibos ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…We found that the suitable concentrations of honeybush for boar semen are similar to those of rooibos [12], although the latter shows a higher TPC and TAC, which is supported by other studies [2,23]. These differences in the TPC between the plant extracts suggest that the protective effects of honeybush on boar sperm may be related to its polyphenol profile, rather than the TPC per se.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We found that the suitable concentrations of honeybush for boar semen are similar to those of rooibos [12], although the latter shows a higher TPC and TAC, which is supported by other studies [2,23]. These differences in the TPC between the plant extracts suggest that the protective effects of honeybush on boar sperm may be related to its polyphenol profile, rather than the TPC per se.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, the honeybush extract (HB3) maintained this sperm parameter unaltered until 120 h of semen storage, showing no differences compared with the CTR group at 0 h. Only the HB1 treatment (200 µg/mL) showed neither positive nor detrimental effects, when compared with the CTR samples, at the different incubation times, although some sperm parameters were enhanced but not significantly. In a previous study [12] using a related plant (rooibos) and at a similar concentration (170 µg/mL), we found a significant decrease in the percentage of motile sperm in comparison with the CTR group at 96 h of semen storage. These differences could be due to the higher TPC found in the rooibos extract.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…As such, the addition of antioxidants to semen extenders has become a standard step in artificial reproduction technologies, although it often increases the final cost of semen doses [ 4 , 6 , 29 , 30 ]. As an alternative, medicinal plants and their products are increasingly recognized worldwide as an alternative source of efficient and cost-effective biomolecules that could be used as supplements during sperm storage [ 5 , 31 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in which the extender was supplemented with different antioxidants reported different effective survival times during the liquid storage of sperms at 17°C. For example, supplementation with rooibos ( Aspalathus linearis ) yields an effective survival time of 96 hr (Ros‐Santaella & Pintus, 2017), whereas supplementation with α‐tocopherol yields an effective survival time of 72 hr (Zakošek Pipan, Mrkun, Nemec Svete, & Zrimšek, 2017). These results indicated that the addition of antioxidants was beneficial for semen quality during liquid storage at 17°C.…”
Section: Discussionmentioning
confidence: 99%